Selective forgetting of self‐threatening statements: Mnemic neglect for dementia information in people with mild dementia. (24th May 2018) - Cheston, Richard; Dodd, Emily; Christopher, Gary; Jones, Charlie; Wildschut, Tim; Sedikides, Constantine
Abstract : Objective: We tested whether people with dementia manifest selective forgetting for self‐threatening information, the mnemic neglect effect (MNE). This selective forgetting is observed among healthy adults in the recall, but not the recognition, of self‐threatening feedback. Methods: Sixty‐four statements about dementia were rated for their level of negativity by 280 staff and students at University of the West of England. The 12 statements rated as most negative and the 12 statements rated as least negative were then read to 62 people with dementia. Participants were randomized to 1 of 2 conditions with the statements referring either to self or to another person. High‐negativity and self‐referent statements had strong threat potential. Participants recalled the statements and then completed a recognition task, which consisted of the 24 previously read statements and 24 new statements. Results: Participants manifested the MNE: They recalled fewer high‐negativity (compared with low‐negativity) statements, but only when these referred to the self rather than another person. This pattern occurred independently of levels of depression or anxiety. Participants also made more self‐protective intrusion errors when the statements referred to the self than another person. Participants did not differ in their recognition of statements. Conclusion: The MNE occurs among people with dementia. The selective forgetting of highly negative, self‐referent statements serves to protect the self against the threat that dementia represents. Given the similarities between the MNE and the clinical phenomenon of repression, the findings may mark psychological processes that are implicated in the acceptance (or lack thereof) of a dementia diagnosis.